Cholangioscope-Assisted Endoscopic Retrograde Appendicitis Therapy for Gangrenous Appendicitis in an HIV-Positive Patient - Li, Qianlong (Turkish Journal of Gastroenterology, 2026)
Cite this article as: Li Q. Cholangioscope-assisted endoscopic retrograde appendicitis therapy for gangrenous appendicitis in an HIV-positive patient. Turk J Gastroenterol. Published online February 23, 2026. doi: 10.5152/tjg.2026.25607.